Improving the Quality of Life of the Elderly through the "Nyaah Ka Kolot" Program - Tri Wahyuningsih; Reini Astuti (Health Notions, 2022)
One of the impacts of the success of health development in Indonesia is increasing the life expectancy of the Indonesian population. Based on Indonesia's population projection data, in 2025 it is estimated to be 33.69 million. In 2030 it is estimated to be 40.95 million and in 2035 it is estimated to be 48.19. Naturally the process of getting old causes a person to experience changes in health problems so health coaching is needed in the elderly group. Many health problems arise due to degenerative diseases due to the ageing process. Therefore, the government together with the community facilitate the elderly group to continue to be able to live independently and productively socially and economically and can maintain and improve their quality of life, one of which is the ‘Nya'ah Ka Kolot’ program. The purpose of this study was to identify the effect of the ‘Nya'ah ka Kolot’ Program on the quality of life of the elderly at the Nursing Center of Batujajar Health Center. The research method used a quasi-experiment with one group pre-posttest without a control design. Respondents were 16 people with the determination of the number of respondents using the replication formula for a completely randomized design. The results of the statistical test showed that the p value of the quality of life on the physical aspect was 0.02, psychological aspects was 0.002, the social aspect was 0.009, and the environmental aspect was 0.002. The conclusion is that there is a significant effect of the Nya'ah ka Kolot program intervention on the quality of life of the elderly. Keywords: quality of life; elderly; Nya’ah Ka Kolot program; nursing center